1,25-Dihydroxycholecalciferol Glycoside (1,25(OH)2D3-G) in Broiler Breeder Diets and Its Influence on Broiler Chicken Growth - Andrade, T. S.; Rohloff Junior, N.; Bebber, B. A.; Pereira, M. F. C.; Maia, M. L. R.; Tesser, G. L. S.; Calderano, A. A.; Vieira, B. S.; Vargas Junior, J. G.; Eyng, C.; Nunes, R. V. (Faculty of Animal Science, IPB University, 2025)
This study aimed to investigate the effects of 1,25-Dihydroxycholecalciferol glycoside (1,25(OH)2D3-G) supplementation on performance, carcass yield, carcass cuts, intestinal histomorphometry, bone health, and gene expression in broiler chickens from broiler breeders. A total of 1,152 one-day-old male Ross 308 AP chicks were distributed in a completely randomized design with a 2 x 3 factorial arrangement. One of the experimental factors was the presence or absence of 1,25(OH)2D3-G (0 or 100 mg/kg) in the diets of broiler breeders between 21 and 30 weeks of age. The second experimental factor consisted of three levels of 1,25(OH)2D3-G supplementation (0, 50, and 100 mg/kg) in the broiler chicken diets from day 1 to day 21, followed by a standard commercial diet from day 22 to day 42. The study totaled six treatments with eight replicates and 24 birds per experimental unit. Performance, carcass and cut yields, as well as tibial breaking strength and composition, were evaluated in broiler chickens at 21 and 42 days. Intestinal histomorphometry and gene expression were assessed at 21 days, while tibial dyschondroplasia was analyzed at 42 days. Broiler chickens from broiler breeders supplemented with 100 mg/kg of 1,25(OH)2D3-G showed higher hatch weight, better feed conversion, improved intestinal morphology, and greater carcass yield. However, this supplementation did not enhance calcium and phosphorus deposition in the tibia, resulting in reduced bone strength. It is concluded that broiler chickens from broiler breeders supplemented with 100 mg/kg of 1,25(OH)2D3-G show better growth performance at 21 and 42 days.